Joint relay and jammer selection in Internet of Things systems - Zhen Li; Tao Jing; Yan Huo (International Journal of Distributed Sensor Networks)
In this article, we consider the physical layer security issue in Internet of Things systems, in which there exist a sensing transceiver pair, a number of candidate nodes, and an eavesdropper. The transceiver pair needs to select a jammer node and a relay node among the candidate nodes so as to preserve the secrecy of the communications. Considering the diversity of candidate channels and the limited available power, it is infeasible to scan all the nodes and find the optimal one. We formulate this jammer and relay selection problem as an optimal stopping problem under a fixed sensing order. Then, through applying dynamic programming solution, we propose a low-complexity approach to obtain the optimal sensing order. The performance of the proposed selection scheme is evaluated through numerical results.